Studi Kelayakan Coffee Class Pada Mase Coffee Lab di Bantul, Yogyakarta - Adita Utami; Fatma Dewi Sinurat; Fransisko Fransisko (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
Coffee Class on Mase Coffee Lab is a business which provides knowledges about coffee industry. The business was founded with basis that there is a growth in interest of coffee and only few similar businesses already exist. With that uniqueness, a research of feasibility study is needed. The aim is to determine the feasibility of the investment that is already ongoing. The data is obtained from either owner and literature study. Then using the data, feasibility study is conducted by analyzing non-financial aspect, financial aspect, continued with further evaluation by doing sensitivity analysis. Non-financial aspect consists of market aspect, technical aspect, management and law aspect also social, economic and environmental aspect. Financial aspect consists of evaluation of Net Present Value (NPV), Payment Back Period (PBP), Benefit to Cost Ratio (BCR) and Internal Rate of Return (IRR). The result obtained are, consecutively, IDR 49,046,768.59, 2 years, 1,21, and 57,84%. Then sensitivity analysis is done for participant numbers, and operational cost. From analysis, it can be concluded that the investment on the business is feasible and it is sensitive to the number of participants.